Pengembangan Wall Chart Materi Jamur Berbasis Potensi Lokal di Ujung Patue, Desa Labotto, Kecamatan Cenrana, Kabupaten Bone - Andi Nurul Adha Andika; St. Syamsudduha; Ummul Hasanah (Universitas Islam Negeri Alauddin Makassar, 2022)
Wall chart media based on local potential are designed by reviewing the aspect of setting proportions and color schemes in the form of schemes, pictures, and charts and their placement on classroom walls and whiteboards using local potential. This research is a Research and Development that aims to develop a wall chart media based on local potential that is valid, practical and effective. This study adapts the development model of Robert Maribe Branch (2009) which consists of several stages namely analyze, design, develop, implement, and evaluate. The target of this study was the 22 students of class X MIPA 1 SMAN 13 Wajo. The research instrument used was a questionnaire to measure practicality and items to measure effectiveness. The results showed that the wall chart media based on local potential was developed on mushroom material had a validity value of 3.54 with a very valid category, the level of practicality showed a very practical category with a total value of 3.52. While the level of effectiveness shows the category is very effective because it reaches 100% completeness value. The implications of this research are: 1) Wall chart media can be used as a media to support learning; 2) Wall chart media is feasible to be applied as a learning medium that can increase activity; and 3) Wall chart media can be implemented in other schools with various biological materials.